Relational Responsibility to Buying Decision: Buyer Perspective in Business of Chinese - Andriany, Lussia Mariesti (Universitas Negeri Malang, 2018)
This research aims to reveal the effect of relational responsibility to buying decision in Chinese business. That ethnic is choosen because of the domination of Chinese in Indonesian business. This research located in major traditional market in Malang, using survey method to collect data through questionnaire instrument. Respondent of this research is buyer of traditional market, amount35 peoples. Sampling technique using in this research is simple random sampling. Validity and reliability test is applied to questionnaire before its distribution to respondents. Data was analyzed through two stages, which were confirmatory analysis factor and simple linier regression. Based on validity and reliability test, all of statement in questionnaire is valid and reliable. From the results of confirmatory analysis, significance value of indicators is below 0.05 which confirms its fit to measure relational responsibility and buying decision.The result of hypothesis testing said that relational responsibility has positive and significant effect to buying decision.